MENTAL ACCOUNTING AND LOSS AVERSION ON INDONESIA FIRM’S PERFORMANCE DURING COVID-19 - Grace Turangan; Sung Suk Kim (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2023)
The world shocked by the found of new virus COVID-19 which impact the firm’s performance. The objective of this study is to examine the effect of mental accounting behavior and loss aversion on the performance of companies in Indonesia listed on KOMPAS100 during the period of pandemic COVID-19. The Ordinary Least Square (OLS) regression model on panel data was formed using the two dependent variables ROA and Tobin’s Q. The results show that loss aversion behavior gives a negative impact on company performance, both on variable ROA and Tobin's Q variables and that behavior generally has an increasing impact when the crisis due to the COVID-19 pandemic occurs. While mental accounting behavior also influence on a negative impact on company performance by using the ROA variable along COVID-19 pandemic period, this behavior significantly increased giving a negative impact on company performance. However, these results are not in line with research using Tobin's Q which shows significant results that mental accounting behavior gives positive impact on company performance and the impact increases when crisis period due to COVID-19 pandemic. The research concluded previous research shows that both mental accounting and loss aversion gave impact to the company performance.